Should agility training for novice badminton players be physically or perceptually challenging? - Dong, M.; Lyu, J.; Hart, T.; Zhu, Q. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Despite its well-known importance in sports, agility is ambiguously defined and lack of research. Shuttle Run (SR) challenges physical quickness and is commonly used to improve the on-court agility of badminton players. In contrast, Reactive Initiation Training (RIT) challenges perceptual quickness, merely demanding rapid initiation of step toward the direction of shuttlecock. METHODS: The current study explores to compare SR with RIT to determine the relative effectiveness of these training on improving the on-court agility of badminton. 20 novice badminton players were split in half to receive either RIT or SR on court for five days. Before and after training, the on-court agility test with and without anticipation was administered. RESULTS: The results showed that both training methods shortened the mean running time, however, only RIT additionally reduced the initiation time and its proportion on those time-consuming positions when agility was assessed without anticipation. CONCLUSIONS: Therefore, the agility training for novice badminton players should be more perceptually than physically challenging to avoid vain effort and unnecessary injuries.